TMEM106B Effect on cognition in Parkinson disease and frontotemporal dementia. Issue 6 (14th May 2019) - Tropea, Thomas F.; Mak, Jordan; Guo, Michael H.; Xie, Sharon X.; Suh, Eunran; Rick, Jacqueline; Siderowf, Andrew; Weintraub, Daniel; Grossman, Murray; Irwin, David; Wolk, David A.; Trojanowski, John Q.; et al.
Abstract : Objective: Common variants near TMEM106B associate with risk of developing frontotemporal dementia (FTD). Emerging evidence suggests a role for TMEM106B in neurodegenerative processes beyond FTD. We evaluate the effect of TMEM106B genotype on cognitive decline across multiple neurogenerative diseases. Methods: We longitudinally followed 870 subjects with diagnoses of Parkinson disease (PD; n = 179), FTD (n = 179), Alzheimer disease (AD; n = 300), memory‐predominant mild cognitive impairment (MCI; n = 75), or neurologically normal control subjects (NC; n = 137) at the University of Pennsylvania (UPenn). All participants had annual Mini‐Mental State Examination (MMSE; median follow‐up duration = 3.0 years) and were genotyped at TMEM106B index single nucleotide polymorphism rs1990622. Genotype effects on cognition were confirmed by extending analyses to additional cognitive instruments (Mattis Dementia Rating Scale‐2 [DRS‐2] and Montreal Cognitive Assessment [MoCA]) and to an international validation cohort (Parkinson's Progression Markers Initiative [PPMI], N = 371). Results: The TMEM106B rs1990622 T allele, linked to increased risk of FTD, associated with greater MMSE decline over time in PD subjects but not in AD or MCI subjects. For FTD subjects, rs1990622 T associated with more rapid decrease in MMSE only under the minor‐allele, rs1990622 C, dominant model. Among PD patients, rs1990622 T carriers from the UPenn cohort demonstrated more rapid longitudinal decline in DRS‐2 scores. Finally, in the PPMI cohort, TMEM106B risk allele carriers demonstrated more rapid longitudinal decline in MoCA scores. Interpretation: Irrespective of cognitive instrument or cohort assessed, TMEM106B acts as a genetic modifier for cognitive trajectory in PD. Our results implicate lysosomal dysfunction in the pathogenesis of cognitive decline in 2 different proteinopathies. ANN NEUROL 2019;85:801–811.